Pengalaman Akseptor Kontrasepsi Suntik 3 Bulan: Experience Of Acceptors Of 3-Month Injection Contraception - Rokhimah, Rokhimah; Aulia, Fika; Lestari, Pratiwi Puji; Amalia, Rizki (Chakra Brahmanda Lentera Institute, 2026)
Three-month injectable contraception is widely used in Indonesia because it is effective, practical, and safe for breastfeeding mothers. However, it has side effects such as emotional disturbances and weight changes that can lead to discontinuation of use. In Banjarmasin City, the Noradina Anggi Agustin TPMB has a relatively high number of three-monthly injectable contraceptive users. This study aims to describe the mothers' experiences as three-monthly injectable contraceptive users at this location. The study used a descriptive qualitative design. The study was conducted at TPMB Noradina Anggi Agustin from December 2025 to January 2026. Six participants, consisting of five acceptors and one midwife, were selected through purposive sampling. The study variables included perceptions, complaints, support, and barriers. The instruments used were the researcher as the main instrument, a semi-structured interview guide, and a voice recorder. The study showed that users of the 3-monthly injectable contraceptive had a positive perception because it was effective in preventing pregnancy and was practical. The main complaints reported were menstrual irregularities, weight changes, and anxiety. Support from husbands, family, and midwives played a significant role in continued use. Barriers identified included fear of needles and fear of using other methods, such as IUDs and implants. This study shows that the experiences of 3-monthly injectable contraceptive users are influenced by their perceptions of contraceptive benefits, perceived side effects, support from their environment, and barriers to contraceptive use. Ongoing counseling by midwives is needed to help users understand side effects and support continued use of 3-monthly injectable contraceptives.